PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KETERAMPILAN MENULIS TEKS PUISI SISWA KELAS X SMK NEGERI 1 TANJUNG RAYA - Sari, Putri Julia; Emidar, Emidar; Rasyid, Yulianti (Universitas Negeri Padang, 2018)
ABSTRACT This research is purpose to describe the influencing of using copy the master technic for writing poetry text ability for students class X SMK Negeri 1 Tanjung Raya. The kind of this research is quantitative. The research uses experiment method which emphasizes on semu design experiment for one group pretest posttest design. There are three result on the research are (1) the students’ ability in writing poetry text before using copy the master technic at SMK Negeri 1 Tanjung Raya is low and grades HC with average 50,40, (2) the students’ ability in writing poetry text after using copy the master technic at SMK Negeri 1 Tanjung Raya is high and grades LdC with average 73,12, and (3) the significant influenced from using copy the master technic writing poetry text ability for students class X SMK Negeri 1 Tanjung Raya. Based on t-test on the significant phase 95% and degrees of freedom (df) = nI because t-table<tcountt (1,70>7,12). Kata kunci: pengaruh, menulis, copy the master, puisi